Photosensitizers Mediated Photodynamic Inactivation Against Virus Particles - Sobotta, Lukasz; Skupin-Mrugalska, Paulina; Mielcarek, Jadwiga; Goslinski, Tomasz; Balzarini, Jan (Mini Reviews in Medicinal Chemistry, 2015)
Viruses cause many diseases in humans from the rather innocent common cold to more serious or chronic, life-threatening infections. The long-term sideeffects, sometimes low effectiveness of standard pharmacotherapy and the emergence of drug resistance require a search for new alternative or complementary antiviral therapeutic approaches. One new approach to inactivate microorganisms is photodynamic antimicrobial chemotherapy (PACT). PACT has evolved as a potential method to inactivate viruses. The great challenge for PACT is to develop a methodology enabling the effective inactivation of viruses while leaving the host cells as untouched as possible. This review aims to provide some main directions of antiviral PACT, taking into account different photosensitizers, which have been widely investigated as potential antiviral agents. In addition, several aspects concerning PACT as a tool to assure viral inactivation in human blood products will be addressed.
Keywords: virus